2007
DOI: 10.1017/s003329170700164x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial on the effectiveness of long-and short-term psychodynamic psychotherapy and solution-focused therapy on psychiatric symptoms during a 3-year follow-up

Abstract: Short-term therapies produce benefits more quickly than long-term psychodynamic psychotherapy but in the long run long-term psychodynamic psychotherapy is superior to short-term therapies. However, more research is needed to determine which patients should be given long-term psychotherapy for the treatment of mood or anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
200
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(205 citation statements)
references
References 42 publications
2
200
0
3
Order By: Relevance
“…Although the limited studies of treatment of depression with psychodynamic psychotherapy have shown promising results (Churchill 2001;Leichsenring 2001;Abbass 2006;Knekt 2008), further research will help to clarify the role this approach can best play in treatment of depression and conflicted anger. In psychodynamic approaches to 5 depression: it is essential that the therapist responds to the a patient's anger in a non-judgemental manner the therapist criticises the patient's anger, to b reduce it with negative feedback the therapist ignores any expression or fantasy c of anger that the patient shows towards them the therapist suggests that anger and d depression are primarily chemically based the therapist focuses on the patient's e problematic beliefs.…”
Section: Role Of Medication In Psychodynamic Treatment Of Anger and Dmentioning
confidence: 99%
“…Although the limited studies of treatment of depression with psychodynamic psychotherapy have shown promising results (Churchill 2001;Leichsenring 2001;Abbass 2006;Knekt 2008), further research will help to clarify the role this approach can best play in treatment of depression and conflicted anger. In psychodynamic approaches to 5 depression: it is essential that the therapist responds to the a patient's anger in a non-judgemental manner the therapist criticises the patient's anger, to b reduce it with negative feedback the therapist ignores any expression or fantasy c of anger that the patient shows towards them the therapist suggests that anger and d depression are primarily chemically based the therapist focuses on the patient's e problematic beliefs.…”
Section: Role Of Medication In Psychodynamic Treatment Of Anger and Dmentioning
confidence: 99%
“…There is evidence supporting the effectiveness of LTDP and psychoanalysis (de Maat et al 2009), especially in long-term follow-ups (Knekt et al 2008(Knekt et al , 2011Huber et al 2013). There is also some indirect evidence that LTDP is superior to other psychotherapies in treating complex patients with chronic depression and previous treatment failures (Leichsenring & Rabung, 2008, 2010Fonagy et al in press).…”
Section: Long-term Dynamic Psychotherapy (Ltdp)mentioning
confidence: 99%
“…Of the studies identified, four were conducted in The Netherlands [20][21][22][23][24], four in the USA [25][26][27][28][29] and one each in Canada, Finland, Denmark, and Japan [30][31][32][33][34]. Ten were randomised controlled trials (RCTs) [20][21][22][23][24][25][26][27][28][29][31][32][33] and two were non-randomised studies (NRSs) with a separate control group [30,34].…”
Section: Study Characteristics (See Appendix 5-electronic Supplementamentioning
confidence: 99%
“…Ten were randomised controlled trials (RCTs) [20][21][22][23][24][25][26][27][28][29][31][32][33] and two were non-randomised studies (NRSs) with a separate control group [30,34]. Studies were conducted in a variety of settings, including workplaces [20,29,30,34], primary care practices [25][26][27][28], occupational health services [21,22,24], and specialty medical clinics [23,[31][32][33].…”
Section: Study Characteristics (See Appendix 5-electronic Supplementamentioning
confidence: 99%